1997
DOI: 10.2134/jeq1997.00472425002600060007x
|View full text |Cite
|
Sign up to set email alerts
|

Diuron and Simazine Losses to Runoff Water in Mediterranean Vineyards

Abstract: The Mediterranean climate is characterized by a hot and dry summer where occasional storm events induce erosion and runoff. The high leaching potential of pesticides to surface waters under such climate conditions are not in relation to the main body of data that originated from summer‐rain row‐crop scenarios. In this 2‐yr study we monitored runoff discharge and concentrations of the two soil applied herbicides diuron [3‐(3,4‐dichlorphenyl)‐1,1‐dimethylurea] and simazine [6‐chloro‐N2,N4‐diethyl‐1,3,5‐triazine‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 0 publications
5
66
0
1
Order By: Relevance
“…Our findings revealed that more than 59% of pesticides are transported during storm events into river systems. Results obtained by previous studies indicate that pesticide transport and losses are related to some phenomena which generally appear close to the application periods (Brown et al, 1995;Lennartz et al, 1997). Moreover, the characteristics of rainfall, runoff volume and storm events have a great impact on pesticide transport and losses (Muller et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…Our findings revealed that more than 59% of pesticides are transported during storm events into river systems. Results obtained by previous studies indicate that pesticide transport and losses are related to some phenomena which generally appear close to the application periods (Brown et al, 1995;Lennartz et al, 1997). Moreover, the characteristics of rainfall, runoff volume and storm events have a great impact on pesticide transport and losses (Muller et al, 2003).…”
Section: Discussionmentioning
confidence: 90%
“…Yields are reduced by the patchy growth and the delay in germination reduces the effective growing seasons (McKissock et al 2000). The water repellency of the topsoil reduces the infiltration capacity of the soil matrix, which can lead to enhanced overland flow and associated soil erosion and nutrient washout (Lennartz et al 1997). This may be particularly the case where heavy rainstorms follow prolonged dry periods, a combination of events that is increasing in frequency and intensity as a consequence of climate change (Cebulak et al 2000).…”
mentioning
confidence: 99%
“…This catchment suffers from serious herbicide pollution of the surface water. Studies on the pollution process show that this pollution should be in relationship with the high risk of herbicide leaching by run-off during the heavy rainfall events that are typical of the area's sub-humid Mediterranean climate (Lennartz et al, 1997;Louchard et al, 2001). They assign a crucial role to the vineyard weed control practices (WCP), which determine both the type and amount of herbicide applied and the evolution of soil surface characteristics that affect the soil's hydraulic conductivity (Leonard and Andrieux, 1998;Hebrard et al, 2006).…”
Section: Fig 1 Location Of the Study Areamentioning
confidence: 99%